Numerical investigation of the lateral load behavior of core and coupled rocking walls - Sari, Ali; Sorosh, Shokrullah (Pontificia Universidad Catolica de Chile, 2022)
During last few decades, the researchers have developed new structural systems which have no or minor damage after being hit by severe events like earthquake. Development of self-centering wall having alternative energy dissipation mechanisms was one of these achievements. A wide variety of rocking wall systems, such as jointed walls, hybrid walls, precast walls with end columns (PreWEC), and PreWEC core wall systems, are proposed and studied. This paper describes an analytical investigation of the lateral load behavior of two new types of hybrid rocking wall systems. Core rocking wall is achieved by merging four single hybrid rocking walls and coupled rocking wall is accomplished by coupling two rocking walls using embedded reinforced concrete beams. The concept of coupling hybrid rocking walls using embedded reinforced coupling beam is emerged from previous coupled conventional shear walls studies. As single rocking wall system, in coupled and core rocking wall, post-tensioning tendons are used as a mean to provide self-centering force, and mild steel bars are used to dissipate energy. The nonlinear behavior of the wall is due to the gap opening at the base joint. Three-dimensional finite element model of each system was developed. The stress distribution, crack propagation, and critical sections of these systems are investigated. The effect of spalling concrete cover in the toe region due to rocking action is explained. In addition, the reduction in stiffness and lateral load resisting capacity of the systems due to cracks is monitored. Finally, the lateral load behavior of single rocking walls is compared to that of core and coupled rocking wall systems.
Keywords: Engineering; Chemical Sciences; coupled rocking wall system; rocking wall; finite element analysis; Civil Engineering; reinforced concrete structures; core rocking wall system